Extensively-Drug Resistant Klebsiella pneumoniae Recovered From Neonatal Sepsis Cases From a Major NICU in Egypt - Hassuna, Noha A.; AbdelAziz, Reem A.; Zakaria, Amira; Abdelhakeem, Mohammed (Frontiers in Microbiology, 2020)
Background Neonatal sepsis is a nuisance to clinicians and medical microbiologists, particularly those cases caused by Klebsiella pneumoniae. Thus, we aimed at investigating the profile and mechanisms of antibiotic resistance and the clonal relationships between K. pneumoniae isolated from neonates at the largest tertiary care hospital’s neonatal intensive care units (NICUs) in Minia, Egypt. Methods This study comprised 156 neonates diagnosed with culture-proven sepsis from February 2019 to September 2019, at a major NICU of Minia City. All K. pneumoniae isolates were collected and characterized by antimicrobial profile, resistance genotype, and pulsed-field gel electrophoresis typing. Results Twenty-four K. pneumoniae isolates (15.3%) were collected out of the 156 sepsis diagnosed neonates. These samples showed extensive drug resistance (XDR) to most of the tested antimicrobials, except fluoroquinolones. All the K. pneumoniae isolates possessed blaVIM and blaNDM carbapenemase genes, while blaKPC gene was detected in 95.8%. Considering extended-spectrum β-lactamases genes, blaCTX–M was found in all the isolates and blaOXA–1 gene in 75% of them. The plasmid-mediated quinolone resistance gene qnrS, was predominantly found among our isolates in comparison to qnrB or qnrA. A moderate degree of clonal relatedness was observed between the isolates. Conclusion To the best of our knowledge, this the first report of an alarming occurrence of XDR among K. penumoniae isolates recovered from neonatal sepsis in Egypt. Our data necessitate proper antimicrobial stewardship as the choices will be very limited.